Omstrukturering af undervisning imod en mere induktiv tilgang - Clark, Alice (Improving University Science Teaching and Learning, 2023)
In my teaching I have experienced that students are reluctant to engage and be active in the class room, which may have adverse effects on their learning. Potential barriers include; large class room setting (approx. 80 students) where students don’t know each other, a deductive organization of the teaching centered around the delivery of de-contextualized general knowledge and definitions, and the availability of the teacher’s slides, containing all the definitions and answers to questions raised by the teacher during class, before class starts. To foster student engagement and to facilitate deep learning of the intended learning outcomes (ILO’s), I restructured the teaching to a more inductive form centered on students’ group work with relatable cases and concrete examples (re-contextualization) promoting personalization of the material in didactic environments supporting students’ own academic insight into the ILO’s through the didactic phases of action, formulation and validation. My role as teachers in this work was primarily to devolve the didactic environments to the students and later to paraphrase students points from interacting with the didactic environment and provide validation (along with the fellow students) and to institutionalize students own insights according with the more general ILO’s. The introduction of Shakespeak clikkers as part of the group work increased students engagement and active participation, and quickly also their understanding of the increasingly more complex examples (still more students answered the quizzes and also got the answers right). The introduction of a pre-class online quiz in Absalon provided insight to students learning based on the curriculum alone (for students as well as the teacher) highlighting the most difficult aspects of the teaching to put extra focus on during the class room teaching. The restructuring of the teaching with case-based relatable examples and quizzes increased student engagement and was highly valuated by the students in the following evaluation.